ANALISIS RISIKO PRODUKSI PADI DAN PENDAPATAN RUMAH TANGGA PETANI PADI DI KAMPUNG SIMPANG ASAM KECAMATAN BANJIT KABUPATEN WAY KANAN - Devira Nurani Sejati; Zainal Abidin; Teguh Endaryanto (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This study aims to analyze the risk of rice production and income of rice farmer households in Simpang Asam Village Banjit District Way Kanan Regency. This study is a survey involving 65 farmers who were selected by using simple random sampling. The primary and secondary data were collected from February to April 2018. The rice production risk is analyzed by calculating variances, standard deviations, and variance coefficients. Household income of rice farmers are obtained from the calculation of income from main farming activity, other farming activities, and non farming activities. The results showed that the production risk was considered in a low category with CV value of. 023. Farmer households income was IDR43,694,613.85, coming from main farming 43.04 percent, other farming 39.25 percent, and non farming activities 17.70 percent.Key words: household income, rice farmers, risk of rice production